PWE-117 'Lies, Damned Lies and The Caecal Intubation Rate' A Study of The Inappropriate Conversion of Incomplete Colonoscopies to Flexible-Sigmoidoscopy. (17th August 2016) - Beg, S; Sansone, S; Ragunath, K
Abstract : Introduction: A caecal intubation rate of >90% is a well accepted quality indicator of colonoscopy and is consequently monitored within endoscopy units. Endoscopists' desire to meet this target may mean that incomplete colonoscopies are recorded as flexible-sigmoidoscopies. The aim of this study was to examine whether the conversion of requested colonoscopies is a clinically significant phenomenon. Methods: A retrospective review of all flexible sigmoidoscopies performed between 1 st January 2015 and 31 st December 2015 at Nottingham University Hospitals was performed. Where a colonoscopy was requested but a flexible-sigmoidoscopy performed, the patient's records and endoscopy reports were reviewed to determine whether this conversion was decided before the start of the procedure and documented. Results: During the 12 month period, 3096 flexible-sigmoidoscopies were performed by 48 endoscopists. 149 requests could not be retrieved and were therefore excluded from this analysis. Of the 2947 sigmoidoscopy requests reviewed, 3.2% (n = 98) procedures were originally requested as a colonoscopy, with 15 converted at the point of vetting. 40 of converted procedures were planned polypectomies or post polypectomy assessments in patients who had previously undergone complete visualisation of the colon, and could therefore be considered appropriate to the intended purpose. 43 conversions occurred in patients who had a valid documented indication for colonoscopy and had undergone full bowel preparation. The most common reasons cited included poor bowel preparation (n = 18), technical failure (n = 12) or clinically inappropriate (n = 8). A clear reason for conversion was not apparent in 5 cases. During the study period 8632 colonoscopies were performed and so conversions represent 0.5% of the total requests. This practice was observed amongst 14 endoscopists, when inappropriate conversions were included in individuals' performance data, 6 endoscopists fell to ≤90% target caecal intubation target. Conclusion: A small, but significant number of colonoscopies are converted to flexible sigmoidoscopies at the time of the procedure. This study demonstrates the conversion of colonoscopy to sigmoidoscopy as being a potential limitation of relying on caecal intubation rate alone. Endoscopy units should consider monitoring the rate of inappropriate conversions to ensure quality is maintained. Disclosure of Interest: None Declared